SMRD: a novel cyber warfare modeling framework for Social Engineering, Malware, Ransomware, and Distributed Denial-of-Service based on a system of nonlinear differential equations - Bouke, Mohamed Aly; Abdullah, Azizol (SABA Publishing, 2024)
Cyber warfare has emerged as a critical aspect of modern conflict, as state and non-state actors increasingly leverage cyber capabilities to achieve strategic objectives. The rapidly evolving cyber threat landscape demands robust and adaptive approaches to protect against advanced cyberattacks and mitigate their impact on national security. Traditional cyber defense strategies often struggle to keep pace with the rapidly changing threat landscape, resulting in the need for more robust and adaptive approaches to protect against advanced cyberattacks. This paper presents a novel cyber warfare modeling framework, Social Engineering, Malware, Ransomware, and Distributed Denial-of-Service (SMRD), capturing the interactions and interdependencies between these core components. The SMRD framework offers insights for enhancing cyber defense, threat prediction, and proactive measures. A mathematical model consisting of a system of nonlinear differential equations is proposed to quantify the relationships and dynamics between the components.